2013
DOI: 10.1186/2193-1801-2-196
|View full text |Cite
|
Sign up to set email alerts
|

Is emphysema a risk factor for pneumothorax in CT-guided lung biopsy?

Abstract: IntroductionComputed tomography (CT)-guided lung biopsy is commonly used to make a histological diagnosis for pulmonary lesions. Its most common complication is pneumothorax. While it is thought that CT-guided lung biopsy should be avoided in patients with emphysema, however, there is no scientific report documenting the relationship the occurrence of pneumothorax and the severity of emphysema.Purpose and methodsTo investigate the relationship between the severity of emphysema and the frequency of pneumothorax… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
24
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 15 publications
4
24
1
Order By: Relevance
“…The increased risk of pneumothorax from emphysema is primarily due to decreased lung elasticity and poor retraction of the lungs, which can easily cause a bulla followed by a pneumothorax. Lesions in contact with the pleura essentially have a depth of 0 cm, and previous studies found that the incidence of pneumothorax was higher when lesions were deeper with 1.0 or 2.0 cm used as cutoff points (15,16,30,(33)(34)(35); however, all of those studies included a depth of 0 cm in the analysis. In this study, we analyzed 607 lesions that had no contact with the pleura (depth ≠0 cm) and found that depth of the lesion was not a significant risk factor of pneumothorax.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…The increased risk of pneumothorax from emphysema is primarily due to decreased lung elasticity and poor retraction of the lungs, which can easily cause a bulla followed by a pneumothorax. Lesions in contact with the pleura essentially have a depth of 0 cm, and previous studies found that the incidence of pneumothorax was higher when lesions were deeper with 1.0 or 2.0 cm used as cutoff points (15,16,30,(33)(34)(35); however, all of those studies included a depth of 0 cm in the analysis. In this study, we analyzed 607 lesions that had no contact with the pleura (depth ≠0 cm) and found that depth of the lesion was not a significant risk factor of pneumothorax.…”
Section: Discussionmentioning
confidence: 88%
“…Only Hiraki (15) thought that the size of the lesion did not correlate with the risk of pneumothorax, which is consistent with the findings of our study. Other researchers have thought that the incidence of pneumothorax was correlated with small lesion size (15,16,25,30,36). Because the accuracy of a biopsy is worse with smaller lesions, a higher number of pleural punctures may be required, which then increases the risk of pneumothorax.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Emphysema was considered mild for ≤25%, moderate for 25%-50%, and severe for >50% score. Only patients with moderate/severe score were deemed positive for emphysema (15).…”
Section: Methodsmentioning
confidence: 99%
“…Pneumothorax is the most frequent complication of this technique. [1][2][3][4] Chest tube placement is associated with higher levels of pain and anxiety, and opioid pre-medication and local anaesthesia is required. 5 The infection risk and inpatient stay increased significantly.…”
Section: Discussionmentioning
confidence: 99%